Site-specific identification and quantitation of endogenous SUMO modifications under native conditions. Issue 1 (December 2017) - Lumpkin, Ryan; Gu, Hongbo; Zhu, Yiying; Leonard, Marilyn; Ahmad, Alla; Clauser, Karl; Meyer, Jesse; Bennett, Eric; Komives, Elizabeth
Abstract Small ubiquitin-like modifier (SUMO) modification regulates numerous cellular processes. Unlike ubiquitin, detection of endogenous SUMOylated proteins is limited by the lack of naturally occurring protease sites in the C-terminal tail of SUMO proteins. Proteome-wide detection of SUMOylation sites on target proteins typically requires ectopic expression of mutant SUMOs with introduced tryptic sites. Here, we report a method for proteome-wide, site-level detection of endogenous SUMOylation that uses α-lytic protease, WaLP. WaLP digestion of SUMOylated proteins generates peptides containing SUMO-remnant diglycyl-lysine (KGG) at the site of SUMO modification. Using previously developed immuno-affinity isolation of KGG-containing peptides followed by mass spectrometry, we identified 1209 unique endogenous SUMO modification sites. We also demonstrate the impact of proteasome inhibition on ubiquitin and SUMO-modified proteomes using parallel quantitation of ubiquitylated and SUMOylated peptides. This methodological advancement enables determination of endogenous SUMOylated proteins under completely native conditions. SUMOylation is post-translational modification implicated in several biological pathways. Here the authors describe an approach for the global profiling of SUMO attachment sites under native conditions that also allows the parallel determination of SUMO and Ub attachments.